Precisely control the morphology and crystallization of temperature-dependent aggregation bulk heterojunction by using co-solvent system for optimized light intensity distribution and its effect on thick active layer polymer solar cells. (1st May 2017) - Zhang, Xiaohua; Zheng, Ding; Xing, Shen; Wang, Hanyu; Huang, Jiang; Yu, Junsheng
Highlights: Morphological, crystalline, electrical properties in active layer are investigated. The light intensity distribution and exciton generation rate are analyzed. High PCE of 9.16% is achieved in a 250 nm thick PSC. Abstract: The effects of co-solvent on the morphology, crystallization and light intensity distribution of thick bulk heterojunction (BHJ) polymer solar cells (PSCs) based on polymer of [(5, 6-difluoro-2, 1, 3-benzothiadiazol-4, 7-diyl)-alt-(3, 3000-di(2-octyldodecyl)-2, 20, 50, 200, 500, 2000-quaterthiophen-5, 5000-diyl)](PffBT4T-2OD):[6, 6]-phenyl-C71-butyric acid methyl ester (PC71 BM) are studied. By adjusting different co-solvent systems in thick BHJ layer, it is found that the polymer crystallization, fullerene absorption and PffBT4T-2OD:PC71 BM BHJ morphology are optimized by using a co-solvent of chlorobenzene (CB):dichlorobenzene (DCB):1, 8-diiodooctanein (DIO). The optimized BHJ thickness of 250 nm is analyzed by using transfer matrix theory, resulting in enhanced FF and PCE of 66.7% and 9.16%, respectively. This phenomenon is due to the active layer can absorb 90% of the incident light with a thickness of 250 nm, which contributes to the light intensity distribution and exciton generation rate.